Gender differences in risk attitudes - Antonio Filippin (IZA World of Labor, 2022)
Many experimental studies and surveys have shown that women consistently display more risk-averse behavior than men when confronted with decisions involving risk. These differences in risk preferences, when combined with gender differences in other behavioral traits, such as fondness for competition, have been used to explain important phenomena in labor and financial markets. Recent evidence has challenged this consensus, however, finding gender differences in risk attitudes to be smaller than previously thought and showing greater variation of results depending on the method used to measure risk aversion.
Keywords: C92; D03; D30; 330; risk aversion; gender gap; risk elicitation methods